Fungi associated with cysts of Globodera rostochiensis, G. pallida, and Heterodera schachtii; and egg masses and females of Meloidogyne hapla in Belgium - Yu, Q.; Coosemans, J. (Phytoprotection, 1998)
Cysts of Heterodera schachtii from sugar-beet (Beta vulgaris) fields and cysts of Globodera rostochiensis and G. pallida from potato (Solanum tuberosum) fields in northern Belgium, as well as egg masses and females of Meloidogyne hapla from a tomato (Lycopersicon esculentum) field in the Flemish-Brabant province, Belgium, were collected and examined for the presence of fungi. Of the total of 374 cysts of H. schachtii, 57.7% were colonized by one or more of 18 different species of fungi, all of which were from the genra Acremonium, Chaetomium, Cylindrocarpon, Fusarium, Gliocladium, Humicola, Mariannaea, Nematophthora, Periconia, Phoma, and Verticillium, and 45.3% of the 726 cysts of Globodera spp. were colonized by one or more of 18 different species, from the same gene. Of the 160 egg masses of M. hapla, 32% were colonized by one or more of 18 species of the genra Arthrobotrys, Cylindrocarpon, Fusarium, Monacrosporium, Paecilomyces, Phoma, Plectosphaerella, and Verticillium, while 31% of the 160 females were colonized by 12 species, from the same gene except Paecilomyces and Plectosphaerella. Fusarium oxysporum was by far the predominant species in both the cyst and root-knot nematodes. A black yeast-like fungus was found in cysts.